Alterations in the intracellular level of a protein subunit of human RNase P affect processing of tRNA precursors - Cohen, Amit (Oxford University Press, 2003)
The human ribonucleoprotein ribonuclease P (RNase P), processing tRNA, has at least 10 distinct protein subunits. Many of these subunits, including the autoimmune antigen Rpp38, are shared by RNase MRP, a ribonucleoprotein enzyme required for processing of rRNA. We here show that constitutive expression of exogenous, tagged Rpp38 protein in HeLa cells affects processing of tRNA precursors. Alterations in the site-specific cleavage and in the steady-state level of 3′ sequences of the internal transcribed spacer 1 of rRNA are also observed. These processing defects are accompanied by selective shut-off of expression of Rpp38 and by low expression of the tagged protein. RNase P purified from these cells exhibits impaired activity in vitro. Moreover, inhibition of Rpp38 by the use of small interfering RNA causes accumulation of the initiator methionine tRNA precursor. Expression of other protein components, but not of the H1 RNA subunit, is coordinately inhibited. Our results reveal that normal expression of Rpp38 is required for the biosynthesis of intact RNase P and for the normal processing of stable RNA in human cells.